The Influence of Marketing Strategy Through Social Media on Retail Business Partner Satisfaction at Soekarno-Hatta Airport - Aditya Pramana; Juliater Simarmata; Prasadja Ricardianto (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to analyze the effect of the independent variables                               (media interactivity, recommending affordance, immersion experience, and credibility perception) on the dependent variable (intention to continue use). Respondents in this study focused on business partners who use airports service company social media. The data used in this study is primary data that comes directly from the object of research. The research sample was selected using a purposive sampling method in order to obtain 150 respondents as the sample. The data analysis used to test the hypothesis is Partial Least Square SmartPLS 4 software PLS-SEM. The results showed that the independent variables (media interactivity, recommending affordance, immersion experience, credibility perception) had a positive effect on the dependent variable (intention to continue use). The results of this study also provide information that the existence of social media for airport service companies will increase the company’s initiative in making breakthroughs in innovation and development of its social media. In addition, social media increases the efficiency of a company, including reducing the burden of communication costs, and can also reduce research costs because social media makes it easy to conduct direct surveys of business partners. With social media, it can also increase the loyalty of retail business partners to airport service companies (brands) that they own.